2015
DOI: 10.1523/jneurosci.2946-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Daily Marijuana Use Is Not Associated with Brain Morphometric Measures in Adolescents or Adults

Abstract: Recent research has suggested that marijuana use is associated with volumetric and shape differences in subcortical structures, including the nucleus accumbens and amygdala, in a dose-dependent fashion. Replication of such results in well controlled studies is essential to clarify the effects of marijuana. To that end, this retrospective study examined brain morphology in a sample of adult daily marijuana users (n ϭ 29) versus nonusers (n ϭ 29) and a sample of adolescent daily users (n ϭ 50) versus nonusers (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 70 publications
9
119
4
Order By: Relevance
“…The susceptibility of axonal connectivity to embryonic CB 1 R loss of function (present report) may persist at later developmental stages in critically susceptible areas, as it has been demonstrated that THC consumption in adolescents can also result in axonal connectivity deficits (29). Nevertheless, in another study, daily marijuana consumption did not induce volumetric changes in several brain areas (30).…”
Section: Discussionsupporting
confidence: 53%
“…The susceptibility of axonal connectivity to embryonic CB 1 R loss of function (present report) may persist at later developmental stages in critically susceptible areas, as it has been demonstrated that THC consumption in adolescents can also result in axonal connectivity deficits (29). Nevertheless, in another study, daily marijuana consumption did not induce volumetric changes in several brain areas (30).…”
Section: Discussionsupporting
confidence: 53%
“…Two other MRI studies have reported that cannabis users had smaller hippocampal volumes than non-users, but that this was not evident in cannabis users with hair samples that were positive for CBD 40,41 . However, the extent to which cannabis use is associated with neuroanatomical changes remains controversial: studies that have matched participants on alcohol use, or have accounted for heritable and genetic risk, have failed to find an association between cannabis use and brain structure [42][43][44] .…”
Section: Psychosismentioning
confidence: 99%
“…And we did not separate gray matter from VOI. Previous studies have reported that there are no change in volume of the NAc structure in patients with prescription opioid dependence (Upadhyay et al, 2010) or marijuana use (Weiland, Thayer, & Depue, 2015). But, Seifert et al (2015) reported that there might be structural differences in the NAc of heroin-dependent patients in comparison with healthy controls.…”
Section: Proton Magnetic Resonance Spectroscopy Is a Noninvasive Neuro-mentioning
confidence: 91%